2011
DOI: 10.1371/journal.pone.0018234
|View full text |Cite
|
Sign up to set email alerts
|

Use-Exposure Relationships of Pesticides for Aquatic Risk Assessment

Abstract: Field-scale environmental models have been widely used in aquatic exposure assessments of pesticides. Those models usually require a large set of input parameters and separate simulations for each pesticide in evaluation. In this study, a simple use-exposure relationship is developed based on regression analysis of stochastic simulation results generated from the Pesticide Root-Zone Model (PRZM). The developed mathematical relationship estimates edge-of-field peak concentrations of pesticides from aerobic soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Examples of the first type are the dispersion of particles and movement through air, which can be modelled by AgDRIFT [77] and Gaussian models [78], soil erosion and sedimentation of runoff [79] and leaching of water-soluble fractions into the soil profile, e.g. Pesticide Root-Zone Model (PRZM) [80] and others [81]. By contrast, multimedia models such as fugacity [82] aim at predicting the concentrations of chemicals in all environmental media.…”
Section: Exposure Assessmentmentioning
confidence: 99%
“…Examples of the first type are the dispersion of particles and movement through air, which can be modelled by AgDRIFT [77] and Gaussian models [78], soil erosion and sedimentation of runoff [79] and leaching of water-soluble fractions into the soil profile, e.g. Pesticide Root-Zone Model (PRZM) [80] and others [81]. By contrast, multimedia models such as fugacity [82] aim at predicting the concentrations of chemicals in all environmental media.…”
Section: Exposure Assessmentmentioning
confidence: 99%
“…Monitoring studies in California showed that the worst‐case exposure concentrations were usually detected in small, static to semi‐static water bodies. For example, in California's Central Valley, one of the nation's most productive agricultural areas, monitoring concentrations are substantially higher in small creeks dominated by irrigation return flows, as compared with larger streams that receive dilution flow from nontreated areas and nonagricultural headwaters (Domagalski and Munday, 2003; Luo et al, 2011). In another study, the Pyrethroid Working Group compiled and analyzed the pyrethroids monitoring data available in the United States and showed that the highest dissolved concentrations detected in agricultural sites were all found in tailwater ditches in California (USEPA, 2016b).…”
Section: Resultsmentioning
confidence: 99%
“…Historically, research models such as RZWQM and Opus were criticized for having high input requirements (Engel et al, 1993; Luo et al, 2011). As environmental data are becoming more accessible to the public, it has become easier to obtain data for many of parameters in these models.…”
Section: Resultsmentioning
confidence: 99%